Advances in Spatial and Temporal Databases 12th International Symposium, SSTD 2011, Minneapolis, MN, USA, August 24-26, 2011, Proceedings - Pfoser, Dieter; Tao, Yufei; Mouratidis, Kyriakos; Nascimento, Mario A.; Mokbel, Mohamed; Shekhar, Shashi; Huang, Yan (Springer eBooks., 2011)
This volume constitutes the refereed proceedings of the 12th International Symposium on Spatial and Temporal Databases, SSTD 2011, held in Minneapolis, USA, in August 2011. The 24 revised full papers presented together with one keynote, 8 short papers, and 8 demonstration papers, were thoroughly reviewed and selected from a total of 63 research submissions, 21 vision and challenges submissions and 16 demonstration submissions. The papers are organized in topical sections on knowledge discovery; spatial networks; access methods; moving objects and sensor networks; multidimensional query processing; and temporal and streaming data.